Comparative Morphometric and Histometric Evaluation of Power-Dependent Tissue Ablation Using Fractional Carbon Dioxide Laser - Ryu HG; Park J; Kim H; Kim W; Lee HR; Ko J; Cho SB (Clinical, Cosmetic and Investigational Dermatology)
Hye Guk Ryu,1,* Jinyoung Park,1,* Hyemin Kim,1 Wanil Kim,2 Hwa-Rim Lee,3 Jeongah Ko,4 Sung Bin Cho5 1Clinical Development Team, Cynosure Lutronic Corporation, Goyang, Korea; 2Department of Biochemistry and Institute of Medical Science, School of Medicine, Gyeongsang National University, Jinju, Korea; 3Department of Pharmacology, School of Medicine, Kyungpook National University, Daegu, Korea; 4Ko Jung A Clinic, Seoul, Korea; 5Yonsei Seran Dermatology and Laser Clinic, Seoul, Korea*These authors contributed equally to this workCorrespondence: Sung Bin Cho, Yonsei Seran Dermatology and Laser Clinic, 224 Siheung-daero, Seoul, 08628, Korea, Tel +82 2-2135-1375, Fax +82 70-8250-1375, Email drsbcho@gmail.comBackground: Fractional carbon dioxide (CO2) lasers are commonly used in dermatological resurfacing, offering precise ablation and controlled dermal remodeling. Although clinical outcomes vary with the energy and pulse settings, comparative morphometric and histometric data on power-dependent tissue interactions are limited.Objective: To evaluate and compare fractional CO2 laser-induced microscopic thermal zones (MTZs) ablation characteristics at peak powers of 30 W and 40 W using an ex vivo porcine skin model.Methods: Ex vivo porcine skin was treated with a fractional CO2 laser at energy levels ranging from 40 to 240 mJ under 30 W and 40 W settings. Frozen tissue was used for dermoscopic assessment of ablation diameters, while unfrozen tissue at physiological temperature (30– 32°C) was analyzed histologically for ablation depth. Morphometric and histometric measurements were performed and statistically analyzed.Results: The 30 W and 40 W settings demonstrated energy-dependent increases in ablation depth and diameter. The 40 W laser consistently generated deeper ablation columns (average 11.8% deeper) with narrower surface diameters (average 7.3% narrower) and reduced peripheral carbonization. Linear regression showed strong correlations between energy and ablation depth (r > 0.91) and diameter (r > 0.91), with higher slope coefficients in the 40 W group, indicating greater ablation efficiency.Conclusion: The 40 W fractional CO2 laser system offers enhanced precision, deeper dermal penetration, and reduced thermal diffusion compared with the 30 W, despite delivering equivalent total energy. These findings suggest that higher peak power settings may improve fractional resurfacing procedures’ safety and clinical outcomes, particularly in populations with darker skin phototypes.Keywords: carbon dioxide, fractional laser, ablation, ex vivo pig skin, histometric evaluation, morphometric evaluation